2023
DOI: 10.1177/1759720x221149963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of giant cell arteritis in patients with newly diagnosed polymyalgia rheumatica – a prospective cohort study

Abstract: Background: It is known that giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) often occur together. So far, the prevalence of GCA in newly diagnosed PMR patients has not been evaluated in a prospective ultrasound study. Objective: The aim of this study was to assess the prevalence of GCA using vascular ultrasound in patients with newly diagnosed PMR. Design: A consecutive cohort of newly diagnosed PMR patients was prospectively evaluated for the presence of GCA with the use of systematic musculoskel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…Effective clinical stratification instruments for primary care are yet to be developed, and it is possible that certain manifestations, such as constitutional symptoms or markedly elevated inflammatory markers, may play a pivotal role in identifying PMR patients with subclinical vasculitis. This assumption is supported by the association of these parameters with large-vessel inflammation in GCA 14…”
Section: Can Pmr Still Be Seen As a Disease Of Primary Care?mentioning
confidence: 69%
“…Effective clinical stratification instruments for primary care are yet to be developed, and it is possible that certain manifestations, such as constitutional symptoms or markedly elevated inflammatory markers, may play a pivotal role in identifying PMR patients with subclinical vasculitis. This assumption is supported by the association of these parameters with large-vessel inflammation in GCA 14…”
Section: Can Pmr Still Be Seen As a Disease Of Primary Care?mentioning
confidence: 69%
“…Es besteht eine Krankheitsverwandtschaft zwischen der Riesenzellarteriitis und der Polymyalgia rheumatica, sodass bei älteren Patienten (>50 Jahre) mit bewegungseinschränkenden bilateralen muskulären Schulter-und Hüftgürtelschmerzen, Morgensteifigkeit und B-Symptomatik (als klinische Indizien für eine Polymyalgia rheumatica) immer auch an eine Riesenzellarteriitis (RZA-Prävalenz unter Patienten mit Polymyalgia rheumatica: 46% [14]) gedacht werden sollte. Die 3 bedeutendsten sonografischen Zeichen der Riesenzellarteriitis sind: ▪ Das "Halo"-Zeichen (im Gefäßquerschnitt darstellbare konzentrische echoarme Gefäßwandauftreibung, welche auch zu einer deutlichen Reduktion der Gefäßquerschnittsfläche führt, in der sich in der farbkodierten Duplexsonografie noch ein erhaltener Blutfluss nachweisen lässt), ▪ das positive Kompressionszeichen (unter Kompression der Arterie bleibt die Gefäßwand aufgrund der entzündlichen Gefäßwandverdickung weiterhin sichtbar), ▪ die pathologische Zunahme des Intima-Media-Komplexes, dessen Messwerte sich mit publizierten Referenzwerten vergleichen lassen [16].…”
Section: Zusatzinfounclassified
“…A systematic review that included imaging with US, positron emission tomography (PET) and MRI concluded that more than a quarter of PMR may have subclinical GCA on imaging 9. Recent US studies have confirmed this finding and suggested that this is a different PMR clinical phenotype, resulting in a different treatment protocol 10 11. A prospective US study that followed patients with PMR for up to 2 years found that those with US-identified subclinical GCA in PMR were almost four times more likely to relapse compared with isolated PMR 12.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular scanning techniques for GCA diagnosis have been optimised and standardised,18 along with the development and validation of a US scoring system by OMERACT for monitoring vascular activity in GCA 17. These advances have led to two robust studies, which were published in 2023 with a combined population of over 400 patients with PMR 10 11. Both studies prospectively examined consecutively enrolled patients with newly diagnosed PMR without any clinical symptoms of cranial GCA.…”
Section: Introductionmentioning
confidence: 99%